CTIM-06. DENDRITIC CELL VACCINE STUDY FOR RECURRENT, HIGH-GRADE GLIOMA: TISSUE-BASED RNA SEQUENCING AND SERUM CYTOKINE LEVELS AS POTENTIAL BIOMARKERS. (9th November 2020) - De La Fuente, Macarena; Koru-Sengul, Tulay; Heros, Deborah; Miao, Feng; Marrero, Alain Fernandez; Tejera, Dalissa; Liendo, Michelle; Khan, Aisha; Ayad, Nagi; Ivan, Michael; Komotar, Ricardo
Abstract: BACKGROUND: Glioblastoma is the most common primary malignant brain tumor. Despite multimodality treatment approach, median progression-free survival (PFS) is only 8 months, median overall-survival (OS) 14 months and 5-year survival rate of under 10%. Dendritic cells (DCs) are the professional antigen presenting cells of the immune system. The rationale for sensitizing dendritic cells to a pool of non-selected tumor antigens is based on the marked heterogeneity present within glioblastoma tumor cells. METHODS: Phase 1/feasibility study of DC vaccine for recurrent high-grade glioma was conducted. Pooled, non-selected tumor antigens collected via tumor cell lysate were used for DC sensitization. RNA sequencing analysis was performed on all tumor samples. Cytokine levels in serum were detected using a Luminex cytokine panel. RESULTS: A total of 20 patients were enrolled onto this study (median age 58yrs, range: 39–74, 65% male). Pathology showed WHO grade IV glioblastoma in 14 (70%) and grade III anaplastic astrocytoma in 6 (30%) patients. IDH wild type in 19 (95%) patients. Treatment emergent adverse events (all grades, regardless of attribution) occurred in more than 15% of the patients (20% fatigue, 15% dizziness, 15% headache, none leading to treatment discontinuation). There were five grade 3–4 and none grade 5 events. One grade 4 event (seizure) probable related to investigational treatment leading to treatment discontinuation. Four grade 3 events (dysphasia, possible related; intracranial hemorrhage unrelated; muscle weakness, unlikely related and hematoma, unrelated). Median PFS was 3.8 months. Median OS was 11 months. RNA sequencing in tumor samples and correlation with cytokine levels in serum is currently been analyzed. CONCLUSION: Tumor lysate pulsed DC vaccination demonstrates acceptable safety and tolerability in high-grade glioma patients. Evaluations of integrating molecular profiling RNA sequencing information and cytokine levels to identify potential subset of patients with significant clinical benefit will be provided.